2012
DOI: 10.1161/circulationaha.112.097295
|View full text |Cite|
|
Sign up to set email alerts
|

Cyclooxygenase-2–Derived Prostacyclin Regulates Arterial Thrombus Formation by Suppressing Tissue Factor in a Sirtuin-1–Dependent-Manner

Abstract: Background-Selective inhibitors of cyclooxygenase (COX)-2 increase the risk of myocardial infarction and thrombotic events, but the responsible mechanisms are not fully understood. Methods and Results-We found that ferric chloride-induced arterial thrombus formation was significantly greater in COX-2 knockout compared with wild-type mice. Cross-transfusion experiments excluded the likelihood that COX-2 knockout platelets, despite enhanced aggregation responses to collagen and thrombin, are responsible for incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 44 publications
8
55
0
Order By: Relevance
“…29 Most recently, it has been recognized that prostacyclin regulates arterial thrombus formation by suppressing tissue factor expression in vasculature, leukocytes, and microparticles. 35 Although it is not precisely known if elevated prostacyclin is the major contributor to thrombosis protection in our mice, the thrombosis phenotype of Bdkrb2 2/2 is not influenced by the phenotype of the bone marrow donor. Our data suggest that host factors, derived from vasculature in the Bdkrb2 2/2 mice, are the major determinant for the thrombosis protection observed.…”
Section: Discussionmentioning
confidence: 80%
“…29 Most recently, it has been recognized that prostacyclin regulates arterial thrombus formation by suppressing tissue factor expression in vasculature, leukocytes, and microparticles. 35 Although it is not precisely known if elevated prostacyclin is the major contributor to thrombosis protection in our mice, the thrombosis phenotype of Bdkrb2 2/2 is not influenced by the phenotype of the bone marrow donor. Our data suggest that host factors, derived from vasculature in the Bdkrb2 2/2 mice, are the major determinant for the thrombosis protection observed.…”
Section: Discussionmentioning
confidence: 80%
“…41 Barberi et al reported that COX-2-deficient mice have decreased Sirt1, enhanced vascular TF expression, and accelerated thrombosis. 31 We observed the opposite in Klkb1 2/2 and Bdkrb2 2/2 mice. Elevated plasma PGI 2 in our mice is associated with increased aortic Sirt1 and KLF4 mRNA and protein that are reduced by nimesulide ( Figure 5C-F).…”
Section: F12mentioning
confidence: 53%
“…Recently COX-2-derived prostacyclin has been recognized to suppress TF expression through the NAD 1 -dependent class III histone deacetylase sirtuin-1 (Sirt1). [29][30][31] The mRNA for both Sirt1 and KLF4 were elevated in Klkb1 2/2 aorta ( Figure 5C). We also found elevated aortic mRNA for Sirt1 and KLF4 in Bdkrb2 2/2 mice 17,18 (supplemental Figure 10).…”
Section: Blood 22 January 2015 X Volume 125 Number 4 the Mas/prostamentioning
confidence: 95%
See 1 more Smart Citation
“…In these mice, the production of PGE 2 was restored as compared with COX-2 knockout mice, whereas no differences were found in PGI 2 metabolites (because their production was mainly COX-2-dependent). 9,15 Interestingly, these mice showed an exaggerate hyperplastic neointimal response when compared with both COX-2 knockout and wild-type mice. Taken together, these results suggest that during COX-2 suppression, the beneficial effects of reducing PGE 2 synthesis in VSMCs and macrophages (recruitment is considerably increased after vascular injury) may greatly overlook the detrimental effects of PGI 2 inhibition and may lead to reduction of neointima.…”
Section: Circulation Research July 5 2013mentioning
confidence: 97%